39-6v=-v-4(8v-3)

Simple and best practice solution for 39-6v=-v-4(8v-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 39-6v=-v-4(8v-3) equation:


Simplifying
39 + -6v = -1v + -4(8v + -3)

Reorder the terms:
39 + -6v = -1v + -4(-3 + 8v)
39 + -6v = -1v + (-3 * -4 + 8v * -4)
39 + -6v = -1v + (12 + -32v)

Reorder the terms:
39 + -6v = 12 + -1v + -32v

Combine like terms: -1v + -32v = -33v
39 + -6v = 12 + -33v

Solving
39 + -6v = 12 + -33v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '33v' to each side of the equation.
39 + -6v + 33v = 12 + -33v + 33v

Combine like terms: -6v + 33v = 27v
39 + 27v = 12 + -33v + 33v

Combine like terms: -33v + 33v = 0
39 + 27v = 12 + 0
39 + 27v = 12

Add '-39' to each side of the equation.
39 + -39 + 27v = 12 + -39

Combine like terms: 39 + -39 = 0
0 + 27v = 12 + -39
27v = 12 + -39

Combine like terms: 12 + -39 = -27
27v = -27

Divide each side by '27'.
v = -1

Simplifying
v = -1

See similar equations:

| -12=10(u-2) | | m^2-2m-21=0 | | 22y=7(3x-6) | | 15/-20 | | -7.17-17.8k=-17.8k-7.17 | | 62+x=84 | | 12.2t+5.93=5.93+12.2t | | -5(x+2)-11=15+4 | | (-96)+x=-55 | | -3j^2+12j+21=0 | | 36-2x=-8(5x+5) | | -12=3(u-2) | | 3x+2(3x-4)=-53 | | -2.04+13.9f+11.87=-1.75+13.9f | | 1/3x-1/2=5 | | 12/4=r/6 | | x-61=30 | | 47+x=-66 | | 8+5r-3=9r+6-3r | | -20c-13=-2-20c-11 | | 24=90n | | 7(6+5n)-7n=-8n+6 | | -3q^2+6q=-123 | | 9x-(4x+6)=2(2x+1) | | -3/4(8-12)=5x-2 | | -57+x=98 | | 7-2(2+3x)=27 | | -57+x=-55 | | -11w-1=-11w | | 10x+9+y=180 | | -(7y+2)-(-6y-7)=2 | | x-124+9x=106 |

Equations solver categories